MODELING THE TENSILE STRENGTH OF CONCRETE WITH POLYETHYLENE TEREPHTHALATE (PET) WASTE AS REPLACEMENT FOR FINE AGGREGATE USING ARTIFICIAL NEURAL NETWORK - WASIU AJAGBE; MURTADHA TIJANI; OLUWAFEMI ODUKOYA (Journal of Engineering Studies and Research)
Tensile strength of concrete made with polyethylene terephthalate (PET) waste as replacement for fine aggregate was modelled using artificial neural network. A multilayer feedforward neural network (MLFFNN) and radial basis function (RBF) methodology were compared to see which was more accurate. The MLFFNN modelling results showed a predictive accuracy of 95.364% and a root mean square error value of 4.4409 × 10-16 while RBF neural network modeling results showed a higher predictive accuracy (99.509%) with a lower root mean square error value (1.6653 × 10-16). It is concluded that ANN models accurately predicted the tensile strength of PET concrete.